Serological detection of anti-leptospira antibodies among animal caretakers, dogs and cats housed in animal shelters in Peninsula Malaysia - ALASHRAF, ABDUL RAHMAN; Bejo, Siti Khairani; Khor, Kuan Hua; Radzi, Rozanaliza; Abdul Rani, Puteri Azaziah Megat; Goh, Soon Heng; Abdul Rahman, Muhammad Sabri; Roslan, Muhammad Azri; Ismail, Rosnah; Lau, Seng Fong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Leptospirosis is a worldwide zoonotic disease caused by Leptospira spp. and it has emerged as one of the major public health issues worldwide. Despite extensive studies, information regarding leptospirosis in animal shelters in Malaysia is still scarce. The aim of this study was to determine anti-Leptospira antibodies and the most common circulating serogroups among humans and animals in animal shelters in west and south parts of Peninsular Malaysia. Blood samples were obtained from 58 humans, 127 dogs, and 47 cats, that were recruited from two shelters. All humans and dogs appeared healthy, except few cats showed clinical signs of mild feline upper respiratory disease. Microscopic Agglutination Test (MAT) was used to detect anti-Leptospira antibodies against 20 pathogenic serovars. Based on the cut-off antibody titre ≥ 1:100, the sero-detection of Leptospira spp. in human, dogs, and cats were as 8.62%, 20.47%, and 14.89%, respectively. Serogroup Bataviae was found in human, dogs and cats, whereas Bataviae, Javanica, and Ballum were the common serogroups among dogs and cats. Anti-Leptospira antibodies titres were in the range from 1:100 to 1:200 in human and 1:100 to 1:400 in sheltered animals. Sero-detection studies of anti-Leptospira antibodies in shelters environment worldwide and regionally is necessary to increase the public health awareness and to understand the risk of this zoonotic disease. Furthermore, data regarding the predominant serogroups is needed in a local setting for further vaccination development studies. More studies are warranted to investigate the role of sheltered animals in leptospiral transmission in its environment.